The Relationship Between Maternal Anxiety and Early Management of Febrile Seizures in Children at RSUP Haji Adam Malik Medan - Ellina Kristina Sihombing; Herna Rinayanti Manurung; Basaria Manurung; Desy Herawati Napitupulu; Cris Anggelina Br Manik; Dia Astami; Nora Vivi Lovelia (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Adolescent girls are individuals who are vulnerable to suffering from anemia due to the menstrual period that occurs every month. In addition, factors suspected to be the cause of anemia in adolescent girls include poor nutritional intake patterns, worm infections, frequent drinking of tea or coffee after meals, prolonged sleep, vitamin C deficiency and economic factors. This study aims to determine the Relationship of Motivation with Compliance of Adolescent Girls in Consuming Fe Tablets at SMPN 1 Tuhemberua, Tuhemberua District, North Nias Regency, North Sumatra Province in 2023. This study is a study with a Cross-sectional design (sectional cut). The number of samples used was 42 people obtained using the Random sampling technique. The data analysis technique used chi-square analysis. The results obtained in this study from 42 respondents, based on a statistical test with a p-value of 0.004 (p-value <0.05), indicate a relationship between motivation and compliance of adolescent girls in consuming iron tablets at SMPN 1 Tuhemberua, Tuhemberua District, North Nias Regency, North Sumatra Province in 2023. It is recommended that health workers increase health promotion to adolescents to prevent anemia in adolescents.